Earthquakes on the surface: earthquake location and area based on more than 14 500 ShakeMaps - Lackner, Stephanie (European Geoscience Union, 2018)
Earthquake impact is an inherently interdisciplinary topic that receives attention from many disciplines. The natural hazard of strong ground motion is the reason why earthquakes are of interest to more than just seismologists. However, earthquake shaking data often receive too little attention by the general public and impact research in the social sciences. The vocabulary used to discuss earthquakes has mostly evolved within and for the discipline of seismology. Discussions on earthquakes outside of seismology thus often use suboptimal concepts that are not of primary concern. This study provides new theoretic concepts as well as novel quantitative data analysis based on shaking data. A dataset of relevant global earthquake ground shaking from 1960 to 2016 based on USGS ShakeMap data has been constructed and applied to the determination of past ground shaking worldwide. Two new definitions of earthquake location (the shaking center and the shaking centroid) based on ground motion parameters are introduced and compared to the epicenter. These definitions are intended to facilitate a translation of the concept of earthquake location from a seismology context to a geographic context. Furthermore, the first global quantitative analysis on the size of the area that is on average exposed to strong ground motion – measured by peak ground acceleration (PGA) – is provided.
Keywords: 25 Ciencias de la Tierra y del Espacio::2507 Geofísica::2507.05 Sismología y prospección sísmica; ODS 11 - Ciudades y comunidades sostenibles